Research on Chewing Gum: Questions of Ethics - Vieira, Sonia (Scientific Research, 2017)
Guidelines for clinical research and ethics committees are significant contributions to decision made in science and law. But since research methods need to follow the changes and the development of science, guidelines for clinical research have to be continuously revised. Many innovations are perceived for their intended beneficiaries as benefits. Unfortunately, this is not always true. Therefore two issues should be mandatory in discussions of research ethics committees: 1) What constitutes a harmful intervention? 2) What procedures should be established for obtaining data and evaluating their relevance? These questions are too broad and there are no ethical solutions that can leap off a paper. But an example can be worked on. Dental caries is a public health challenge in any country and chewing gum may have an effect with respect to plaque reduction, at least in a short period of time. But sugar chewing gum cannot be used as a positive control in biomedical researches. However, trials referred herein allocated participants for a sugar chewing gum group. Therefore, the aim of this critical review is to emphasize that such a procedure is an example of a conscious disregard for the consideration which is due to trial participants. Were these desirable researches themselves or they had other purposes?
Keywords: Research Methods; Ethics in Research; Chewing Gum; Chlorhexidine